Interaksi Sosial dalam Keberagaman Umat Muslim Masyarakat Giri Asih, Gunung Kidul Yogyakarta - Muhadi, Muhadi (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
In the discussion of contemporary religious issued, the discourse of religious pluralism was one of the most hotly debated themes; it was born amid the diversity of the exclusive truth claimed and truth claimed that were inclusive attitude of looking at the reality of religious plurality. Plurality was a reality in Indonesia, ethnic diversity, culture, religion, and class made much difference. The difference was a necessity that must be respected, but it was not rare to find some social conflicts underlying racial issues, namely the conflict between religious groups or religious sectsâ conflict. However, the existence of diversity and that diversity should be valued and mutual respect between one another, create a harmonious life in religious plurality.